2016
DOI: 10.1021/acssensors.6b00043
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free Nanopore Single-Molecule Measurement of Trypsin Activity

Abstract: Trypsin is the most important digestive enzyme produced in the pancreas, and is a useful biomarker for pancreatitis. In this work, a rapid and sensitive method for the quantitative determination of trypsin activity is developed by using a biological alpha-hemolysin protein nanopore. Due to its much larger molecular diameter than the narrow pore constriction, trypsin itself cannot transport through the alpha-hemolysin channel. Hence, an indirect trypsin detection method is developed by monitoring its proteolyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 46 publications
1
49
0
Order By: Relevance
“…0.15 M NaCl ( cis )/3 M NaCl ( trans )), or a greater applied voltage (e.g. +200 mV), as well as other engineered αHL nanopores, as documented in our previous studies .…”
Section: Resultssupporting
confidence: 71%
“…0.15 M NaCl ( cis )/3 M NaCl ( trans )), or a greater applied voltage (e.g. +200 mV), as well as other engineered αHL nanopores, as documented in our previous studies .…”
Section: Resultssupporting
confidence: 71%
“…They demonstrated LF detection down to 10 n m . Trypsin‐based cleavage studies have also been reported by several groups . Figure C shows nanopore detection of trypsin activity on amyloid beta peptides as detected by a mutated form of the αHL pore (M113F) 7 .…”
Section: Peptide Sensingmentioning
confidence: 67%
“…After single connector was inserted and then the translocation signals of R11 or R12 peptide were observed under −50 mV, the trypsin was added and mixed into the cis-chamber while recording the data until the majority of R11 or R12 was digested. [51]…”
Section: Methodsmentioning
confidence: 99%